Development of Model for Professional Competency Assessment (PCA) in Vocational Education: Study of the Engine Tune-Up Injection System Assessment Scheme - Nurtanto, Muhammad; Arifin, Zainal; Sofyan, Herminarto; Warju, Warju; Nurhaji, Soffan (Journal of Technical Education and Training, 2020)
The field legality of expertise for job applicants in the field of vocational education is one of the strong considerations. This recognition can obtain through accredited professional institutions such as the Professional Certification Institute (PCI), which operates independently. The problem arises that PCI in the automotive sector consists of several providers (PCI-TO, PCI- INA, PCI- TOP, etc.), and different levels (the 1st Party PCI, 2nd Party PCI, and 3rd Party PCI) so the quality is not the same and requires the right solution. As a result, the automotive PCI requires a reference standard as a professional competency test model standard. This study aims to test and produce a professional competency test model in automotive clusters, namely engine tune-up injection system (ETU-IS), that meet the characteristics and can be applied. The development subjects consist of PCI-TOP informants, Indonesian Training Center in Bandung (BBLKI), and P4TK BOE/VEDC in Malang as automotive competency experts. Instrument validation consists of construction, validation and feasibility test of the instrument. Data analysis uses alpha coefficients and Inter-Rater statistics. The findings of the study are (1) the assessment of professional competency standard assessment on ETU-SI using a Competency-Based Assessment approach in the form of work instructions, including case studies, demonstrations, and interviews that meet the criteria; (2) the fulfillment of instruments related to competency dimensions in aspects of competency testing consisting of TS, TMS, CMS, EMS, and JRES; and (3) verification of the infrastructure and facilities as well as the competency test the ethical requirements such as impartiality and delivery of recommendations have appropriate decision. The new finding in this study is that appraiser’s behavior is the key to success in the implementation of competency tests, so technical and methodological abilities require as professional competency examiners.